PERAN ORANG TUA DAN GURU DALAM KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA EDUKATIF KELAS 1 MIS AL-ABROR - Mabruroh Mabruroh; Wahyu Setyo Nugroho; Andi Wapa; Nasiruddin F (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2026)
This study aims to analyze the roles of parents and teachers in improving children's early reading skills through the use of educational media. This study used a qualitative approach with data collection techniques including observation, unstructured interviews, and documentation. The study subjects consisted of teachers and parents of elementary school students. The results showed that children's early reading skills improved after the use of educational media, as indicated by the ability to recognize letters, understand sounds, and read syllables and simple words. Teachers acted as facilitators, motivators, and guides, creating a fun learning environment through the use of educational media such as letter flashcards and picture books. Meanwhile, parents played a role in providing home learning support, motivation, and providing simple learning media. The use of educational media has proven effective in increasing children's interest and engagement in reading. However, there are obstacles such as limited parental time and differences in student abilities. Therefore, effective collaboration between teachers and parents is necessary to optimize children's early reading skills.